Caracterização de poliformos em comprimidos distribuídos pela Secretaria de Saúde de Araraquara por difração de raios X - Tita, Diego Luiz [UNESP] (2014)
The presence of polymorphic structures not expected in the composition of solid drugs can generate differences in physical and chemical properties such as chemical reactivity, apparent solubility, dissolution rate, among others, thus affecting its bioavailability. These unwanted changes can compromise the efficacy, safety and quality of the product and therefore compromising medical treatment. In this work, the objective was to identify and quantify the phases presents in their compositions through the Rietveld method in data of X-ray powder diffraction the medicines: hydrochlorothiazide, furosemide, spironolactone, carbamazepine, phenytoin and phenobarbital. It was observed in all analyzed samples, with the exception of similar spironolactone 25 mg (ES25S), the crystalline form of the active ingredient were equal to those presented in the literature as being the ideal for the manufacture of tablets. In the case of ES25S, was identified as the active principle hydrated form of spironolactone, which according to the literature, presents a lower dissolution compared to form II, which is used in the manufacture of medicines due to its greater diuretic activity. In addition, the sample of furosemide (FUS) was quantifying the crystalline active principle present in the composition of a tablet through the inclusion of an internal standard method. It was found that a tablet FUS contains an average of 35.92 mg crystalline furosemide. Intrinsic dissolution studies were performed for carbamazepine tablets where it was observed that similar medicine (CB200S1) in the first fifteen minutes of the experiment has a higher dissolution (~ 90 %) than the maximum limit proposed by the Brazilian Pharmacopoeia is 75 %.